COMPARAÇÃO DE ÍNDICES DE APTIDÃO FÍSICA ENTRE ESTUDANTES NA CIDADE DE CÁCERES-MT (Fiep Bulletin - online, 2017)
This study aimed to compare the levels of physical fitness among students in the city of Caceres, Mato Grosso, comparingperformance between students from public and private schools. For this survey was conducted including 87 students, aged 11 and 12years, male and female, 49 students of Public School and 38 students Private School, using the tests and measures battery (GAYA ,2005), weight (body mass), Height (Height), BMI (body mass Index), Build, Abdominal, Horizontal Leap (Force Upper Extremities)Medicinebol (Strength Upper Extremities), Flexibility, Agility, Speed, Member Resistance superiors General and resistance. Also thequestionnaire was used to identify the main living habits, divided into socioeconomic characterization, everyday organization, socioculturalparticipation and sports practices. It was found that for most tests there was little significant difference only in the flexibility testwas verified significance between the two schools, a fact explained by the great difference in the level of education of parents and thepattern of family life. The results of other tests were balanced, BMI (Body Mass Index) proved to be within the normal range for the vastmajority of students. Compared to the Standards Table nationally referenced to sportspeople, between Genders, there were positiveresults for Strength testing of the lower limbs and resistance, and negative for flexibility.
Keywords: Physical education; physical assessment; motor performance